Surveillance and Monitoring of Dialysis Access. (22nd November 2011) - Kumbar, Lalathaksha; Karim, Jariatul; Besarab, Anatole
Abstract : Vascular access is the lifeline of a hemodialysis patient. Currently arteriovenous fistula and graft are considered the permanent options for vascular access. Monitoring and surveillance of vascular access are an integral part of the care of hemodialysis patient. Although different techniques and methods are available for identifying access dysfunction, the scientific evidence for the optimal methodology is lacking. A small number of randomized controlled trials have been performed evaluating different surveillance techniques. We performed a study of the recent literature published in the PUBMED, to review the scientific evidence on different methodologies currently being used for surveillance and monitoring and their impact on the care of the dialysis access. The limited randomized studies especially involving fistulae and small sample size of the published studies with conflicting results highlight the need for a larger multicentered randomized study with hard clinical end points to evaluate the optimal surveillance strategy for both fistula and graft.